Occupational exposure to selected isocyanates in Polish industry - Sławomir Brzeźnicki; Marzena Bonczarowska (Nofer Institute of Occupational Medicine, 2015)
Background: Isocyanates constitute a group of highly reactive, low molecular weight chemicals used worldwide for polyurethane manufacturing. The occupational exposure to these compounds is a major cause of occupational asthma, thus it is very important to monitor their concentration in the workplace atmosphere. The aim of the study was to measure the concentration of 4,4'-methylenediphenyl diisocyanate (MDI; CAS 101-68-8), toluene-2,4-di-isocyanate (2,4-TDI; CAS 584-84-9), toluene-2,6-di-isocyanate (2,6-TDI; CAS 91-08-7) and hexamethylene di-isocyanate (HDI; CAS 822-06-0) in the work environment for evaluation of the occupational exposure to these compounds. Material and Methods: Determination of concentrations of selected isocyanates was carried out in 21 manufacturing plants, during different industrial processes. The collected air samples (personal samples) were analyzed by means of the high-performance liquid chromatography (HPLC). Results: The presented results represent the 1st data on the occupational exposure to isocyanates in Poland. This set of data is generally indicative of concentrations of analyzed isocyanates that are low and do not exceed the maximum admissible concentration (MAC) values in Poland. Elevated concentrations (above the MAC value) were found only for the TDI in the course of manufacturing of polyurethane foam blocks. Conclusions: Results of many studies show that low concentrations of isocyanates (particularly of low volatility like for example MDI) in the air cannot exclude the possibility of additional absorption of these compounds through skin. Taking into consideration all the uncertainties associated with the evaluation of the risk of exposure to isocyanates based solely on measurement of their levels in the air, it would seem that the simultaneous application of environmental and biological monitoring would only facilitate a reliable assessment of the occupational exposure risk. Med Pr 2015;66(3):291-301